Sodium danshensu attenuates cerebral ischemia-reperfusion injury by targeting AKT1 - Qing Gao; Hao Deng; Zhengfei Yang; Qiuyue Yang; Yilin Zhang; Xiaopeng Yuan; Miao Zeng; Maojuan Guo; Wenyun Zeng; Xijuan Jiang; Bin Yu (Frontiers Media S.A., 2022)
The beneficial properties of Sodium Danshensu (SDSS) for controlling cerebral ischemia and reperfusion injury (CIRI) are elucidated here both in vivo and in vitro. SDSS administration significantly improved the viability of P12 cells, reduced lactate dehydrogenase (LDH) leakage, and decreased the apoptosis rate following exposure to an oxygen-glucose deprivation/reoxygenation (OGD) environment. In addition, the results of a HuprotTM human protein microarray and network pharmacology indicated that AKT1 is one of the main targets of SDSS. Moreover, functional experiments showed that SDSS intervention markedly increased the phosphorylation level of AKT1 and its downstream regulator, mTOR. The binding sites of SDSS to AKT1 protein were confirmed by Autodock software and a surface plasmon resonance experiment, the result of which imply that SDSS targets to the PH domain of AKT1 at ASN-53, ARG-86, and LYS-14 residues. Furthermore, knockdown of AKT1 significantly abolished the role of SDSS in protecting cells from apoptosis and necrosis. Finally, we investigated the curative effect of SDSS in a rat model of CIRI. The results suggest that administration of SDSS significantly reduces CIRI-induced necrosis and apoptosis in brain samples by activating AKT1 protein. In conclusion, SDSS exerts its positive role in alleviating CIRI by binding to the PH domain of AKT1 protein, further resulting in AKT1 activation.